2021
DOI: 10.1136/bmjgast-2021-000739
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes in COVID-19 and cirrhosis: a systematic review and meta-analysis of observational studies

Abstract: BackgroundCOVID-19 continues to pose a significant healthcare challenge throughout the world. Comorbidities including diabetes and hypertension are associated with a significantly higher mortality risk. However, the effect of cirrhosis on COVID-19 outcomes has yet to be systematically assessed.ObjectivesTo assess the reported clinical outcomes of patients with cirrhosis who develop COVID-19 infection.Design/MethodPubMed and EMBASE databases were searched for studies included up to 3 February 2021. All English … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 64 publications
1
20
0
Order By: Relevance
“…In addition, several evidence suggested that liver injury is associated with a more severe SARS-CoV-2 infection [ 6 8 ], especially when liver damage was defined by raised AST [ 5 ]. The presence of liver damage was also shown to represent a negative prognostic factor for COVID-19 patients [ 9 , 10 ]. However, previous studies on COVID-19 patients mostly used liver transaminases to define liver damage and to describe its association with mortality risk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several evidence suggested that liver injury is associated with a more severe SARS-CoV-2 infection [ 6 8 ], especially when liver damage was defined by raised AST [ 5 ]. The presence of liver damage was also shown to represent a negative prognostic factor for COVID-19 patients [ 9 , 10 ]. However, previous studies on COVID-19 patients mostly used liver transaminases to define liver damage and to describe its association with mortality risk [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This systematic review has several strengths. Unlike previous meta-analyses on related topics [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], this study: (i) involves a comprehensive analysis of a large number of studies that are based in different countries in the world; (ii) includes many articles that were published in 2021, after the introduction of the Delta strain; (iii) analyzes only peer-reviewed data; (iv) assesses the extensive analysis of the source of the heterogeneity and bias in the studies; and (v) compares the risk of admission to the ICU vs. no admission among hospitalized COVID-19 patients, and is stratified on the basis of comorbidities and demographic status.…”
Section: Discussionmentioning
confidence: 92%
“…However, the associations with other comorbidities have been less clear, such as with cancer, chronic liver disease, diabetes, and kidney disease. While several meta-analyses studies report an increased risk of death in COVID-19 patients with diabetes [ 5 , 11 , 19 ], cancer [ 20 , 21 , 22 ], liver disease [ 23 , 24 , 25 ], and kidney disease [ 26 , 27 , 28 , 29 ], some report the lack of correlation between these comorbidities and the disease progression or the clinical outcomes of COVID-19 patients [ 30 , 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…cirrhosis, independent of etiology, have an approximately 80% elevated risk of all-cause mortality compared to non-cirrhotic patients (22). The mortality among liver transplantation candidates is more than 30% and reaches 45% among those with decompensated cirrhosis and high MELD scores (23).…”
Section: Accepted Manuscriptmentioning
confidence: 99%